Efektifitas Penerapan Pidana Kurungan Bagi Pelaku Penyalahgunaan Narkotika - Zainab Ompu Jainah (Law Faculty of Universitas Bandar Lampung, 2015)
Act number 35 in 2009 provides severe criminal sanction for narcotic abuser in forms of imprisonment and fine sanctions. However, the narcotic abusers are in fact increasing. This is caused by criminal sentencing that does not provide deterrent effect for the narcotic abusers. The problems in this research were how did the effectiveness of imprisonment for the narcotic abusers. This research used normative and empirical jurisdiction approaches. Data were collected with literary and field studies. Data were analyzed qualitatively. The results showed that: effectiveness of imprisoning sentence for narcotic abuser so far was not effective. The researcher suggests the Indonesian Minister of Law and Human Right to provide enough structure and infrastructure, to build new facilities of Department of Corrections, department of Correction should prepare its officers with trainings related to narcotics and cooperate with National Narcotics Agency